Analisis User Experience Web halal Batam Di Pusat Kajian Halal Politeknik Negeri Batam Menggunakan User Experience - Dimas Surya Fitriansyah; Riwinoto Riwinoto (Politeknik Negeri Batam, 2021)
The web is a technology currently being developed in various fields, one of which is in the field of tourism, but in the world of tourism it is still not widely used. Batam Halal Web, is one example of the use of web technology in the field of halal tourism in the city of Batam. The limitations of using brochures as promotional media or information make the web one of the best promotional and information media to use today. This study uses the User Experience Questionaire method to analyze users of the Batam Halal Web application against the community or tourists in the city of Batam which will later produce data related to the level of user experience quality for the Batam Halal Web application. The results of the User Experience measurement for the Batam Halal Web Application get results that are above the average on the attractiveness parameters (1.43), perspicuity (1.54), dependability (1.36), and novelty.(1.08, while the efficiency (1.53) and stimulation (1.41) aspects are in the good category.